Covered airway stent placement for malignant tracheobronchial strictures in patients with an endotracheal tube. Issue 11 (November 2016) - Kim, M.J.; Shin, J.H.; Park, J.-H.; Kim, J.H.; Song, H.-Y.; Park, J.; Cho, Y.C.; Kim, S.H.
Abstract : Aim: To evaluate the technical feasibility and safety of covered airway stent placement for malignant tracheobronchial strictures in patients with an endotracheal tube. Materials and methods: Data regarding retrievable, expandable, metal stent placement under fluoroscopic guidance in 20 patients with an endotracheal tube inserted for malignant tracheobronchial strictures were retrospectively analysed. The clinical effectiveness was assessed using the following variables: technical and clinical success; procedure and stent-related complications; and duration of intubation following stent placement. Results: Stent placement was technically successful in all 20 patients (100%), and with 19 of the 20 patients (95%) showing symptomatic improvement within 5 days. The endotracheal tube could be removed during ( n =7) or after ( n =12) stent placement, and the mean duration of intubation following stent placement was 1.4 days (range 0–3 days). One patient could not have his endotracheal tube removed and he died 9 days following stent placement in an intubated state. There were no procedure-related complications. Stent-related complications in three patients included partial ( n =2) and complete ( n =1) stent migration, all of which were managed with placement of a second stent ( n =2) or stent removal and placement of a second stent ( n =1). Conclusion: Covered airway stent placement under fluoroscopic guidance in patients with an endotracheal tube inserted for malignant tracheobronchial strictures, is both technically feasible and safe. Highlights: Stent placement using an endotracheal tube is effective and safe for patients with malignant tracheobronchial strictures. Stent placement via an endotracheal tube has a high technical success rate without procedure-related complications. The endotracheal tube could be removed depending on the patient's condition after stent placement.